Shatavari: An excellent intercrop option in orchards - Saran, P L; Kalariya, K A; Meena, R P; Singh, Susheel; Devi, Ganga (Indian Horticulture, 2023)
Medicinal plants growing in forests require partial shade, moist soils rich in organic matter, high relative humidity and mild temperatures. Shatavari is grown in open land as well as under shade conditions at low altitudes. Tolerances of plants under shade condition sustain growth due to increase in photosynthetic capacity per unit of light and sugar content. Shade leaves made an efficient use of the less intense irradiation reaching up to them.